2011
DOI: 10.1158/0008-5472.can-10-2372
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction–Mediated Import of MicroRNA from Bone Marrow Stromal Cells Can Elicit Cell Cycle Quiescence in Breast Cancer Cells

Abstract: Bone marrow (BM) metastasis of breast cancer (BC) can recur even decades after initial diagnosis and treatment, implying the long-term survival of disseminated cancer cells in a dormant state. Here we investigated the role of microRNAs (miRNA) transmitted from BM stroma to BC cells via gap junctions and exosomes in tumor cell quiescence. MDA-MB-231 and T47D BC cells arrest in G 0 phase of the cell cycle when cocultured with BM stroma. Analyses of miRNA expression profiles identified numerous miRNAs implicated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
306
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(317 citation statements)
references
References 44 publications
11
306
0
Order By: Relevance
“…It is well established that gap junctions contribute to cell homeostasis by allowing the intercellular exchange of essential growth regulators, including ions, nucleotides, sugars, small peptides, RNAs (Kardamia et al, 2007;Vinken et al, 2011), and microRNAs (Lim et al, 2011). Cx26 expression is virtually absent in the normal adult airway epithelium (Chanson, Koval, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that gap junctions contribute to cell homeostasis by allowing the intercellular exchange of essential growth regulators, including ions, nucleotides, sugars, small peptides, RNAs (Kardamia et al, 2007;Vinken et al, 2011), and microRNAs (Lim et al, 2011). Cx26 expression is virtually absent in the normal adult airway epithelium (Chanson, Koval, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…74 A separate study found that multiple miRNAs were transferred from bone marrow stromal cells to nearby breast cancer cells upon seeding to the bone. 75 MiR-127, miR-197, miR-222 and miR-223, all direct inhibitors of CXCL12, were shown to directly transfer from stromal cells into cancer cells via gap junctions or through secreted exosomes. The transfer of these miRNAs decreased cancer cell proliferation and could represent a mechanism for tumor quiescence within the bone microenvironment.…”
Section: Mirna Regulation Of Tumor-stromal Interactions During Bone Mmentioning
confidence: 99%
“…Lately miRNA has also become implicated in signaling between stromal and epithelial cells and some recent reports [28,29] have provided evidence suggesting that traffic of miRNA subtypes between disseminated cancer cells and bone marrow stromal cells can influence whether the cancer cells establish metastatic colonies or remain in dormant state. If these findings are corroborated, it will show that non-proteinaceous molecules also convey signals between interacting cell populations in the tumor microenvironment, which can determine whether tumor cells can fulfill an already activated, intrinsic potential towards malignant behavior.…”
Section: Ii) Cancer Formation: Microscopic and Cellular Aspectsmentioning
confidence: 99%